Rhizobium meliloti exopolysaccharides: genetic analyses and symbiotic importance. (August 1991) - Reuber, T. Lynne; Reed, Jason; Glazebrook, Jane; Glucksmann, M. Alexandra; Ahmann, Dianne; Marra, Andrea; Walker, Graham C.
Abstract : Summary Genetic experiments have indicated that succinoglycan (EPS I), the acidic Calcofluor-binding exopolysaccharide, of the nitrogen-fixing bacterium Rhizobium meliloti strain Rm1021 is required for nodule invasion and possibly for later events in nodule development on alfalfa and other hosts. Fourteen exo loci on the second megaplasmid have been identified that are required for, or affect, the synthesis of EPS I. Mutations in certain of these loci completely abolish the production of EPS I and result in mutants that form empty Fix - nodules. We have identified two loci, exoR and exoS, that are involved in the regulation of EPS I synthesis in the free-living state. Certain exo mutations which completely abolish EPS I production are lethal in an exoR95 or exoS96 background. Histochemical analyses of the expression of exo genes during nodulation using exo :: Tn phoA fusions have indicated that the exo genes are expressed most strongly in the invasion zone. In addition, we have discovered that R. meliloti has a latent capacity to synthesize a second exopolysaccharide (EPS II) that can substitute for the role(s) of EPS I in nodulation of alfalfa but not of other hosts. Possible roles for exopolysaccharides in symbiosis are discussed.